A high ratio of G1 to G0 phase cells and an accumulation of G1 phase cells before S phase progression after injurious stimuli in the proximal tubule. Issue 10 (7th October 2014) - Iwakura, Takamasa; Fujigaki, Yoshihide; Fujikura, Tomoyuki; Ohashi, Naro; Kato, Akihiko; Yasuda, Hideo
Abstract Proximal tubule (PT) cells can proliferate explosively after injurious stimuli. To investigate this proliferative capacity, we examined cell cycle status and the expression of cyclin‐dependent kinase inhibitor p27, a G1 phase mediator, in PT cells after a proliferative or injurious stimulus. Rats were treated with lead acetate (proliferative stimulus) or uranyl acetate (UA; injurious stimulus). Isolated tubular cells were separated into PT and distal tubule (DT) cells by density‐gradient centrifugation. Cell cycle status was analyzed with flow cytometry by using the Hoechst 33342/pyronin Y method. Most PT and DT cells from control rats were in G0/G1 phase, with a higher percentage of PT cells than DT cells in G1 phase. Lead acetate and UA administration promoted the G0‐G1 transition and the accumulation of G1 phase cells before S phase progression. In PT cells from rats treated with lead acetate or a subnephrotoxic dose of UA, p27 levels increased or did not change, possibly reflecting G1 arrest. In contrast, p27 became undetectable before the appearance of apoptotic cells in rats treated with a nephrotoxic dose of UA. The decrease in p27 might facilitate rapid cell cycling. The decreased number of p27‐positive cells was associated with PT cell proliferation in renal tissues after a proliferative or injurious stimulus. The findings suggest that a high ratio of G1 to G0 phase cells and a rapid accumulation of G1 phase cells before S phase progression in the PT is a biological strategy for safe, timely, and explosive cell proliferation in response to injurious stimuli.